El duque de Ripperdá según Antonio Ferrer del Río: un intento olvidado de nacionalización - Alfonso Calderón Argelich (Cuadernos de Ilustración y Romanticismo)
The literary critic and historian Antonio Ferrer del Río (1814-1872) published a single novel: De patria en patria (1861), a dramatization of the Duke of Ripperdá flight through Europe and Morocco after his infamous dismissal as Secretary of State of Philipp V of Spain. The plot is based on the biographical account written by Salvador José Mañer in 1740. Ferrer del Río made significant changes that transformed this eighteenth-century adventurer into a romantic hero. This article studies the orientalist and Cervantine literary resources that allowed to fit this historical character into the national narrative of Spanish liberal conservativism.